1990
DOI: 10.1017/s001447970001824x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Five Years of No-tillage and Mulch on Soil Properties and Tuber Yield of Cassava on an Acid Ultisol in South-eastern Nigeria

Abstract: The effect of no-tillage and mulch on soil properties and tuber yield of cassava was studied over a five year period on an infertile, add Ultisol in south-eastern Nigeria. Mulch was applied at a rate of 12 t ha' 1 as a split application once at planting and once six months after planting. No chemical fertilizers were used during the trial. Bulk density and proportion of micropores (pore radius, r, <1.4 ftm) were greater, and proportion of macropores (r>14.4 j»m) lower, with notillage. Water infiltration was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…The mean annual rainfall is 2400 mm in a monomodal distribution lasting from March to November. The soil at the experimental site is derived from coastal sediments and classified as loamy, siliceous, isohyperthemic, Typic Paleudult [9]. Selected physical and chemical properties are shown on Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The mean annual rainfall is 2400 mm in a monomodal distribution lasting from March to November. The soil at the experimental site is derived from coastal sediments and classified as loamy, siliceous, isohyperthemic, Typic Paleudult [9]. Selected physical and chemical properties are shown on Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In Africa application of mulch, especially that of leguminous species, increased cassava yields in acid sandy soils (Ofori, 1973;Hulugalle et al, 1991). In sandy soils on the Atlantic Coast of Colombia, Cadavid et al (1998) reported that annual applications of 12 t ha −1 of dry Panicum maximum grass as mulch significantly increased cassava yields during eight consecutive years of cropping, especially in the absence of chemical fertilizers.…”
Section: Green Manures Cover Crops and Mulchmentioning
confidence: 99%
“…In all treatments, the impact on lowering soil temperature was more pronounced at the end than at the beginning of the growing season. Hulugalle et al (1986) reported that incorporation of 12 t ha -1 of Siam weed (Eupatorium odor- For personal use only.…”
Section: Soil Moisture and Temperature During The Growing Seasonmentioning
confidence: 99%